1986
DOI: 10.1016/0014-5793(86)80176-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel calcium‐binding protein (CP22) in multidrug‐resistant murine and hamster cells

Abstract: Analysis of cytoplasmic extracts of multidrug-resistant murine and hamster cells by SDS gel and 2D gel electrophoresis showed that they expressed an abundant 22 kDa protein which was absent from the drug sensitive parent lines. SDS gel electrophoresis in the presence of EGTA and direct binding tests with 45Ca2+ showed that the resistance-associated protein is a specific calcium-binding protein. Thus the development of multidrug resistance in both coic~cine-blats hamster cells and ad~amycin-sel~ted murine cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…Antibodies to membranes from cells activated with phorbol 12-myristate 13-acetate (PMA) (which stimulates both the NADPH oxidase and degranulation) were used in the present study to probe cytosol from unstimulated cells, thus identifying proteins common to both, including those which translocate. Here we focus on the identification of a novel 28 kDa protein distributed throughout the cell, which exhibits strong sequence similarity to sorcin, a calcium-binding protein which is over-expressed in certain multi-drug-resistant cell lines (Koch et al, 1986;Van der Bliek et al, 1986;Meyers et al, 1987 Preparation and fractionation of neutrophils Neutrophils were prepared from leukopheresis samples of patients with chronic granulocytic leukaemia (CGL), from buffycoat residues obtained from the South London Blood Transfusion Centre, Tooting, London S.W. 17, U.K., or from venous blood obtained from normal subjects (Segal & Jones, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies to membranes from cells activated with phorbol 12-myristate 13-acetate (PMA) (which stimulates both the NADPH oxidase and degranulation) were used in the present study to probe cytosol from unstimulated cells, thus identifying proteins common to both, including those which translocate. Here we focus on the identification of a novel 28 kDa protein distributed throughout the cell, which exhibits strong sequence similarity to sorcin, a calcium-binding protein which is over-expressed in certain multi-drug-resistant cell lines (Koch et al, 1986;Van der Bliek et al, 1986;Meyers et al, 1987 Preparation and fractionation of neutrophils Neutrophils were prepared from leukopheresis samples of patients with chronic granulocytic leukaemia (CGL), from buffycoat residues obtained from the South London Blood Transfusion Centre, Tooting, London S.W. 17, U.K., or from venous blood obtained from normal subjects (Segal & Jones, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using in vitro derived multidrugresistant (MDR) cell lines have shown that MDR is often associated with over-production of two groups of proteins: the P-glycoproteins (for review see which have drug-binding properties (Safa et al, 1986) and are thought to function as a membrane anchored efflux pump for multiple drugs (Willingham et al, 1986); and sorcin/CP22 (Meyers et al, 1985;Meyers & Biedler, 1981;Koch et al, 1986;Martinnson et al, 1985;Shen et al, 1986a; Van der Bliek et al, 1986a), a small cytosolic calcium-binding protein. Considerable evidence supports the hypothesis that it is P-glycoprotein that is responsible for MDR in almost all cell lines examined (Debenham et al, 1982;Gros et al, 1986;Kartner et al, 1983;Robertson et al, 1984;Scotto et al, 1986;Shen et al, 1986b;Van der Bliek et al, 1986b).…”
mentioning
confidence: 99%
“…By far the most striking membrane alteration in several MDR cells is the presence of a high molecular weight glycoprotein family (P-glycoprotein) (Juliano & Ling, 1976;Biedler & Peterson, 1981;Kartner et al, 1983). In addition to P-glycoprotein hyperexpression, a small acidic cytosolic protein called V19 (Meyers & Biedler, 1981), CP22 (Koch et al, 1986) or Sorcin ( Van der Bliek et al, 1986), has also been noted in some hamster and mouse MDR cell lines. Although the role of this protein is uknown, it is able to bind calcium with high affinity (Koch et al, 1986) Riordan and Ling (1979), or by ultrasonic disintegration for 5 sec at 4°C using a MSE sonicator, model 1276, amplitude setting 22 microns.…”
mentioning
confidence: 99%
“…In addition to P-glycoprotein hyperexpression, a small acidic cytosolic protein called V19 (Meyers & Biedler, 1981), CP22 (Koch et al, 1986) or Sorcin ( Van der Bliek et al, 1986), has also been noted in some hamster and mouse MDR cell lines. Although the role of this protein is uknown, it is able to bind calcium with high affinity (Koch et al, 1986) Riordan and Ling (1979), or by ultrasonic disintegration for 5 sec at 4°C using a MSE sonicator, model 1276, amplitude setting 22 microns. After disruption or sonication the following differential centrifugation steps were applied: nuclear spin, 300 g for 10min at 4"C; mitochondrial spin, 4000g for 10min at 4 C; microsomal spin, 35,000g for 30min at 4°C.…”
mentioning
confidence: 99%
See 1 more Smart Citation